日本海側の鮮新統～更新統産北方系Macoma属(二枚貝)の分類と分布 - 天野, 和孝; アマノ, カズタカ; Amano, Kazutaka (上越教育大学, 1996)
秋田県男鹿半島安田海岸の中部更新統鮪川層から化石として初めて Makoma lama meridionalis Scarlatoを発見した。また，本亜種はすでに石川県金沢市の下部更新統大桑層からMacoma calcana（Gmelin），M．nasuta（Conrad），Macoma praetexta（v．Martens）として報告されていることも明らかにした。オホーツク・ベーリング要素としては，本亜種とM.middendoriffi Dallのみが日本海沿岸域の鮮新統～更新統に認められた。また，現在日本海に生息するMacomaの北極海・北大西洋要素の多くは更新世後期以降に日本海に移動した可能性が高い。 Some fossil specimens of Macoma (Macoma) lama meridionalis Scarlato were firstly obtained from the middle Pleistocene Shibikawa Formation at Anden of Akita Prefecture. This subspecies were illustrated from the early Pleistocene Omma Formation in Ishikawa Prefecture as Macoma calcarea (Gmelin), M. nasuta (Conrad) and M. praetexta (v. Martens) by Kaseno and Matsuura (1965), Matsuura (1992) and Ogawawara (1977). Nipponopagia ommaensis was proposed by Ogasawara (1977) , based on the specimens from the Omma Formation. However, as pointed by Petrov (1982), this species is synonymous with the Recent Macoma (Macoma) middendorffi Dall. Moreover, Gastrana yantaiensis (Crosse and Debeaux) illustrated by Yokoyama (1926) from the beds A at Anden (= Shibikawa Formation?) is also conspecific with Macoma middendorffi. Except for Macoma calcarea, the following boreal species of Macoma are now living in the Japan Sea: Macoma lama meridionalis, M. middendorffi, "M. orbiculata Scarlato", M. moesta (Deshayes) , M. balthica (Linne), M. loveni (Steenstrup) and M. crassula (Deshayes) . As the result of this study, the first two species which distribute mainly in the Okhotsk and Bering Seas have been known from the Plio-Pleistocene strata in the Japan Sea borderland. On the other hand, the latter four species are now living in the North Pacific, Arctic and North Atlantic. Their fossil records are restricted to the Pleistocene of North America and Europe. Therefore, these four species probably migrated in the Japan Sea after late Pleistocene. departmental bulletin paper